Randomised controlled trial of two methods of weaning from high frequency positive pressure ventilation. Issue 6 (June 1989) - Greenough, A; Pool, J; Gamsu, H
Abstract : Forty preterm infants suffering from respiratory distress syndrome were entered into a randomised controlled trial to assess the importance of the length of inspiratory time during weaning from high frequency positive pressure ventilation (HFPPV). Two weaning regimes were compared: in one (group A) inspiratory time was limited to 0.5 seconds throughout weaning, in the other (group B) ventilator rate was reduced by increasing both inspiratory and expiratory time (inspiration:expiration ratio constant) until inspiratory time reached 1.0 seconds. At ventilator rates of 20 and 40 breaths/minute an acute comparison was made in all 40 infants of the two inspiratory times; despite the lower mean airway pressure associated with the shorter inspiratory time blood gases were maintained. There was no difference in the incidence of pneumothoraces or need for reventilation between the two regimens but infants in group A had a shorter duration of weaning. We conclude limitation of inspiratory time to 0.5 seconds during weaning from HFPPV is advantageous to preterm infants with respiratory distress syndrome.